A robust optimization based approach for microgrid operation in deregulated environment. (15th March 2015) - Gupta, R.A.; Gupta, Nand Kishor
Highlights: RO based approach developed for optimal MG operation in deregulated environment. Wind uncertainty modeled by interval forecasting through ARIMA model. Proposed approach evaluated using two realistic case studies. Proposed approach evaluated the impact of degree of robustness. Proposed approach gives a significant reduction in operation cost of microgrid. Abstract: Micro Grids (MGs) are clusters of Distributed Energy Resource (DER) units and loads. MGs are self-sustainable and generally operated in two modes: (1) grid connected and (2) grid isolated. In deregulated environment, the operation of MG is managed by the Microgrid Operator (MO) with an objective to minimize the total cost of operation. The MG management is crucial in the deregulated power system due to (i) integration of intermittent renewable sources such as wind and Photo Voltaic (PV) generation, and (ii) volatile grid prices. This paper presents robust optimization based approach for optimal MG management considering wind power uncertainty. Time series based Autoregressive Integrated Moving Average (ARIMA) model is used to characterize the wind power uncertainty through interval forecasting. The proposed approach is illustrated through a case study having both dispatchable and non-dispatchable generators through different modes of operation. Further the impact of degree of robustness is analyzed in both cases on the total cost of operation of the MG. A comparative analysis between obtained results using proposed approach and other existing approach shows the strength of proposed approach in cost minimization in MG management.